2021
DOI: 10.3390/s21144749
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Deep Convolutional Neural Networks Applied for Prediction of Plant Leaf Diseases

Abstract: In the modern era, deep learning techniques have emerged as powerful tools in image recognition. Convolutional Neural Networks, one of the deep learning tools, have attained an impressive outcome in this area. Applications such as identifying objects, faces, bones, handwritten digits, and traffic signs signify the importance of Convolutional Neural Networks in the real world. The effectiveness of Convolutional Neural Networks in image recognition motivates the researchers to extend its applications in the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(116 citation statements)
references
References 114 publications
0
91
0
1
Order By: Relevance
“…Convolutional neural networks are constructed by using several convolution layers which use learnable filters or kernels to identify patterns in images such as edges, texture, color, and shapes. CNN models possess several desirable properties that enable the extraction of complex features in images that would otherwise be hard to distill [ 26 ]. Since the success of AlexNet in the ImageNet large-scale image classification competition, several variants of CNNs have been invented that explore a variety of approaches to overcome the limitations of the standard CNN models [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Convolutional neural networks are constructed by using several convolution layers which use learnable filters or kernels to identify patterns in images such as edges, texture, color, and shapes. CNN models possess several desirable properties that enable the extraction of complex features in images that would otherwise be hard to distill [ 26 ]. Since the success of AlexNet in the ImageNet large-scale image classification competition, several variants of CNNs have been invented that explore a variety of approaches to overcome the limitations of the standard CNN models [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among pretrained models with more than a certain number of layers, a model with a large number of hyperparameters such as ResNet50 has good analysis performance. If precise tuning of hyperparameters was involved, the accuracy was relatively higher than that of the model with deeper layers (Dhaka et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, year after year, errors are reduced and accuracy is increased by changing the layer composition, depth, and calculation methods used in CNNs. In previous studies, several applications of CNN architectures showed outstanding results in the competition in the past decade (Dhaka et al, 2021 ) such as AlexNet (Krizhevsky et al, 2012 ), VGG19 (Simonyan and Zisserman, 2014 ), Inception v3 (Szegedy et al, 2016 ), Inception v4 (Szegedy et al, 2017 ), GoogLeNet (Szegedy et al, 2015 ), and ResNet50 (He et al, 2016 ), DenseNet121 (Huang et al, 2017 ), and SqueezeNet (Iandola et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the introduction of deep learning has led to significant advances in object recognition. There are many scholars who have applied deep learning methods in agriculture, including yield estimation by detecting fruits and improving crop quality by pest and disease detection (Gao et al, 2020;Mu et al, 2020;Dhaka et al, 2021;Kundu et al, 2021). Mu et al (2020) developed an R-CNN algorithm using Resnet-101 as the backbone network for the detection, counting, and size estimation of green tomatoes.…”
Section: Introductionmentioning
confidence: 99%